Efektivitas Peran Kelompok Tani Terhadap Kinerja Tani Budi Padi di Kelurahan Kemumu Kecamatan Arma Jaya Kabupaten Bengkulu Utara - Putra, Arma; Putri Suci Asriani; Musriyadi Nabiu (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
Farmer groups have an important role in agricultural activities, such as learning classes and vehicles for cooperation and production units. However, in practice there are still some obstacles, such as the infrequency of farmer groups to carry out farming activities and carry out farming activities together. The purpose of this study was to analyze the performance of rice farming, process innovation, the effectiveness of the farmer groups role ant its role on the performance of rice farming directly and through process innovation. The data sources used are primary processed descriptively qualitatively and quantitatively using the SEM-PLS approach. The results of the analysis show that the performance of rice farming, process innovation is in the high category and the effectiveness of the role of farmer groups is in the effective category. Analysis of the influence of the effectiveness of farmer groups on the performance of rice farming yielded negative results but not significant. While the indirect effect states that the role of farmer groups has a positive and significant effect on the performance of rice farming through process innovation. Based on a comparison of direct and indirect effects, process innovation is the biggest contributor to improve the performance of rice farming. With these results, farmer groups must still be able to improve the realization of their role so that farmers as members of farmer groups can still improve farming performance and farmer groups must be more active in overcoming various farming problems.